2019
DOI: 10.2478/aoas-2018-0053
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of FTO and PLIN2 Polymorphisms in Relation to Carcass and Meat Quality Traits in Pigs

Abstract: the aim of this study was to analyze the association of polymorphisms in alpha-ketoglutarate-dependent dioxygenase (FTO) and perilipin 2 (PLIN2) genes with carcass and meat quality traits in pigs reared in poland. the research covered 578 sows that belong to the following breeds: Duroc, Hampshire, Polish Landrace, Pietrain, Puławska and Polish Large White. FTO (fm244720:g.400c>g) and PLIN2 (gu461317:g.98g>A) genes variants were determined by means of pcr-rflp and Acrs-pcr methods respectively. Association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…In the previous study, PLIN2 stimulates long chain fatty acid uptake and regulates metabolism of intracellular lipid droplets (Gao and Serrero, 1999;Conte et al, 2016;Polasik et al, 2019). And expression analysis showed the presence of PLIN2 transcripts in seven tested pig tissues with high expression found in adipose tissue and skeletal muscle (Davoli et al, 2011;Polasik et al, 2019). These results provide evidence that PLIN2 gene is a candidate gene for IMF.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In the previous study, PLIN2 stimulates long chain fatty acid uptake and regulates metabolism of intracellular lipid droplets (Gao and Serrero, 1999;Conte et al, 2016;Polasik et al, 2019). And expression analysis showed the presence of PLIN2 transcripts in seven tested pig tissues with high expression found in adipose tissue and skeletal muscle (Davoli et al, 2011;Polasik et al, 2019). These results provide evidence that PLIN2 gene is a candidate gene for IMF.…”
Section: Discussionsupporting
confidence: 59%
“…Statistical analysis indicated that G6714C was significantly associated with the NPPC color score, G6813A, and G10340A significantly affected NPPC color score and NPPC marbling score, and G10632A significantly affected BF (p < 0.05). In the previous study, PLIN2 stimulates long chain fatty acid uptake and regulates metabolism of intracellular lipid droplets (Gao and Serrero, 1999;Conte et al, 2016;Polasik et al, 2019). And expression analysis showed the presence of PLIN2 transcripts in seven tested pig tissues with high expression found in adipose tissue and skeletal muscle (Davoli et al, 2011;Polasik et al, 2019).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The c. 2 151 * 479C > T substitution showed a statistically significantly higher marbling score for the meat of CC homozygotes than that of CT heterozygotes and TT homozygotes. Another study, conducted on pigs of the Landrace, Large White and Pulawska breeds, showed an association between polymorphism in the 3'UTR region of the perilipin-2 gene (PLIN2) and the quality characteristics of meat (Polasik et al 2019). In all breeds, the researchers confirmed the presence of the GG genotype, which was distinguished by a statistically significantly higher content of intramuscular fat (from 0.054% in White Large to 0.123% in Pulawska).…”
Section: Reviewmentioning
confidence: 92%
“…Moreover, the meat is generally softer and tender when the birds are slaughtered at early ages (Berri, 2000). In general, body and muscle composition change with age since protein, fat, and dry matter percentages increase over time (Aberle et al, 2001;Yamak et al, 2020).…”
Section: Introductionmentioning
confidence: 99%